THE POSITIVE AND NEGATIVE EFFECTS OF COMPUTER GAMES ON HUMAN PSYCHOLOGY - Muhayyo Jalilova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The international popularity of computer games includes the notion that they have inspired films, music, literature, and fashion compositions. Computer games play an important role in developing logical thinking, strategic planning, and problem solving. . These games also help in developing analytical skills and improving memory. As computer games become more popular, so do social problems. Issues of gaming addiction, influence on aggressive behavior, and social isolation become the subject of discussion and research. In this case, it is important to use the pros and cons.